The degree of verb movement in embedded clauses in three varieties of Norwegian - Bentzen, Kristine (Nordlyd, 2007)
The position of the verb(s) in embedded non-V2 contexts varies in Norwegian dialects. In Eastern Norwegian (EastN), all verbs have to follow all adverbs in non-V2 contexts. In Tromsø Northern Norwegian (TrNN) main verbs and non-finite auxiliaries have to follow all adverbs, but finite auxiliaries may precede adverbs they take scope over. In Regional Northern Norwegian (ReNN) all finite verbs (main/auxiliary) may precede all adverbs, and non-finite auxiliaries may precede adverbs they take scope over. These data are accounted for within a remnant movement approach. The variation between the three dialects is argued to follow from differences in how selectional features on auxiliaries and T are checked. It is suggested that auxiliaries are associated with a pair of functional projections (so-called lifters): a VP lifter below and an AdvP lifter above. An auxiliary with these lifters ‘sinks’ below adverbs it takes scope over. Overt feature checking (through adjacency) occurs when the lifters are present; covert feature checking occurs when the lifters are absent. In EastN, overt feature checking, and the lifters, is obligatory for all auxiliaries; in TrNN this is obligatory for non-finite auxiliaries but optional for finite auxiliaries; in ReNN this is optional for all auxiliaries.